Pengaruh Pemberian Reinforcement terhadap Hasil Belajar Kosakata Bahasa Mandarin Siswa TKB Picket Fence Pre-School - Marlim, Yenny; Winner, Patricia (Journal of Language, Literature and Teaching, 2019)
The goal of this research was to find the effect of reinforcement on the kindergarten B students’ learning achievement in Mandarin vocabulary. The researcher used quantitative with quasiexperiment type and pre-test and post-test design. The sample of this research was all of the kindergarten B students at Picket Fence Pre-School, specifically experimental group consisted of 20 students and control group 20 students. The hypothesis was that there was an effect of reinforcement on students’ learning achievement in Mandarin vocabulary. The t-test result showed that reinforcement had a significant effect on students’ achievement in vocabulary. The post-test result in experimental group was 87,5; while the post-test in control group was 79,5. It was found that tcount bigger ttable with tcount was 2 while ttable was significantly 5% with dk = 38 that was 1,69. Thus, Ha was accepted and Ho was rejected. Based on the explanation above, it was concluded that reinforcement had a significant effect on kindergarten B students’ learning achievement in Mandarin vocabulary at Picket Fence Pre-School.